2017
DOI: 10.1155/2017/5968618
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model of Gastric Inflammation and Treatment with Cobalamin

Abstract: Pernicious anaemia (PA) is an autoimmune condition where antibodies target intrinsic factor and parietal cells, reducing the patient's ability to absorb cobalamin promoting atrophic gastritis. Treatment guidelines are based on excretion data of hydroxocobalamin from healthy individuals obtained 50 years ago. This manuscript describes the use of phorbol 12-myristate 13-acetate (PMA) to stimulate low grade inflammation in an epithelial colorectal cell line to assess the efficacy of methylcobalamin and hydroxocob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…2 Other transition metals have been explored in cancer therapy, such as ruthenium 2a,2b,3 osmium, 2c rhodium, 4,5a and iridium, 5 but nonplatinum anticancer drugs in clinical use remain predominantly organic. In particular, despite the high natural abundance of cobalt 6 and the extensive synthetic chemistry of its complexes, there are, to the best of our knowledge, so far no cobalt compounds in widespread clinical use other than vitamin B 12 (cobalamin), 7 though the cobalt(III) imine complex CTC-96 (Doxovir) has been explored as a treatment for herpes simplex virus, 8 reaching phase II clinical trials. 8b…”
Section: Introductionmentioning
confidence: 99%
“…2 Other transition metals have been explored in cancer therapy, such as ruthenium 2a,2b,3 osmium, 2c rhodium, 4,5a and iridium, 5 but nonplatinum anticancer drugs in clinical use remain predominantly organic. In particular, despite the high natural abundance of cobalt 6 and the extensive synthetic chemistry of its complexes, there are, to the best of our knowledge, so far no cobalt compounds in widespread clinical use other than vitamin B 12 (cobalamin), 7 though the cobalt(III) imine complex CTC-96 (Doxovir) has been explored as a treatment for herpes simplex virus, 8 reaching phase II clinical trials. 8b…”
Section: Introductionmentioning
confidence: 99%
“…Our patient responded well to parenteral vitamin B12 and steroid therapy. Vitamin B12, given as hydroxocobalamin, has also been shown to reduce the gastric inflammatory process as well as retard the development of immune dysfunction associated with HIV/AIDS [14,15]. On the other hand, short course steroid therapy was given as adjunct treatment, as it has been shown that corticosteroids improve vitamin B12 absorption by reducing gastric inflammation [16].…”
Section: Discussionmentioning
confidence: 99%